Cryptocurrency in the perspective of Shariah - Naim, Abdul Rahaman (2018)
The purpose of this study is to investigate one of the types in Fintech area, which is cryptocurrency from the perspective of Shariah. Until now, there are around 1,600 types of cryptocurrencies around the world. However, one of the most sought cryptocurrency in Malaysia is Bitcoin. Since it is still a new in Malaysia, the in-depth study on this has not yet been fully completed. By the realization to study this issue, a research has been conducted to become an eye-opener for those who want to dig deeper to gain the knowledge about this especially on the views from Islamic perspective or to be specific, from Shariah views. On the other hand, many issues arise regarding this cryptocurrency especially bitcoin. Therefore, this research will investigate the concept of money with its characteristics, and analyze if cryptocurrency does have all the characteristics of real money in it. Move forward to the next objective, this study will also explain on the Islamic perspective, and to be exact, Shariah views of cryptocurrencies as the currency or as a medium of exchange. Until now, there is still not much current views from the current scholars on this exact matters. Most of the views are regarding on whether their countries accepting it to be used or not, and the majority are the views from the government. Still, there is no specific hukm on the uses of cryptocurrencies. So, the outcome of this study will provide an important insight for potential customers who still want to invest their money in cryptocurrencies.